Penggunaan Analogi Perpindahan Panas â Perpindahan Massa Untuk Mengukur Koefisien Perpindahan Panas Benda Berbentuk Sembarang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The measurements of convective heat transfer coefficients of particles with arbitrary shapes were conducted by heat and mass transfer analogy. The effects of particle orientations relative to the air flows were also investigated. The particles were made of naphthalene. The mass transfer coefficients were calculated from the mass loss of the particles, and the heat transfer coefficients were estimated by heat and mass transfer analogy. The result shows a very good agreement with the existing Nu - Re correlation. It concludes that the technique is valid and reliable for particles of any shape. Further applications of the technique for estimating heat transfer coefficients are justified.